Design principles and basic algorithmic support of remote health monitoring systems for cardiovascular patients - A. S. Krasichkov (Известия высших учебных заведений России: Радиоэлектроника)
Construction principles of remote health monitoring systems for cardiovascular patients are presented. Basic algorithmic support of the system that allowscarrying out detection and sorting of cardiocomplexes with simultaneous accumulation of identical cardiocomplexes is determined.